P369 Efficacy of infliximab after failure of subcutaneous anti-TNF agents in patients with ulcerative colitis: A multicentre study. (16th January 2018) - Streichenberger, A; Pariente, B; Bozon, A; Arab, N; Amiot, A; Vuitton, L; Tilmant, M; Nachury, M; Altwegg, R; Delasalle, T; Gagnière, C; Grégoire, B; et al.
Abstract: Background: After infliximab (IFX), which was the first anti-TNF available in ulcerative colitis (UC), subcutaneous (SC) anti-TNF i.e. adalimumab (ADA) or golimumab (GOLI) were approved in UC. While SC anti-TNF were less effective after failure of IFX, there are no data on the efficacy of IFX after ADA or GOLI failure in UC. We aimed to evaluate the efficacity of IFX after failure or intolerance to SC anti-TNF and to identify the factors associated with therapeutic efficacy. Methods: This was a retrospective multicentre study (7centres), including all UC patients who received IFX after a SC anti-TNF. Efficacy was assessed according to physician's judgement as failure, partial response or complete response. Mucosal healing (MH) was defined as Mayo endoscopic subscore ≤1. Clinical and biological response was defined as persistent response under IFX at week 52 without steroids or colectomy and with CRP < 5 mg/l. Results: Overall, 80 UC patients were included (E1 = 10.1 %), E2 = 36.7 % and E3 53.2 %). Among them, 70 were treated previously with ADA (87.5%), 63.9% discontinued ADA due to primary failure, 29.1% due to loss of response (LOR) and 7.1% due to adverse event (AE). ADA was intensified in 42 patients (60.0%). Thirteen patients received prior GOLI. Median Mayo score at inclusion was 9.5 [8.11]. The patients were treated with IFX and concomitant use of 5-ASA (10.3 %), steroids (29.5%), thiopurines (46.2 %) or methotrexate (12.8 %). At week 12, the rate of clinical response was 78.4% (36.5% of complete response). IFX was intensified in 44.1% of the patients within the first 12 weeks. IFX was stopped in 17 patients, 13 because of primary failure and 4 due to AE. MH was observed in 33.3% of the patients. In multivariate analysis, prior anti-TNF LOR rather than primary failure (OR = 6 [1.2 −30.8], p = 0.033) and concomitant use of thiopurines (OR = 2.5 [1.1–12.5]) were predictive of clinical response at W12. At week 52, the remission rate was 29.2% (21 of 72). Clinical response was achieved in 61.1% of patients (40.3% of complete response). IFX was intensified in 2/3 of the patients. IFX was stopped in 24 patients due to failure ( n = 18) or AE ( n = 6). MH was achieved in 63.3% of patients (19/30). In multivariate analysis, clinical response at week 12 was associated with clinical remission at week 52 (OR = 25 [1.4–46.0]). At last follow-up, (mean follow-up 44 months), the rate of clinical and biological response was 30.6% (22/72), 47.2 % of patients were still treated with IFX (73.6% with intensified doses) and 11 patients (13.8%) required colectomy. Conclusions: The results suggest that UC patients may be successfully treated with IFX after failure of SC anti-TNF, as approximately 50% of them maintained long-term clinical response.